CIE L*a*b*: comparison of digital images obtained photographically by manual and automatic modes - Takatsui, Fabiana [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Neisser, Maximiliano Piero; Borelli Barros, Luiz Antonio [UNESP]; Monteiro Loffredo, Leonor de Castro [UNESP] (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2012)
The aim of this study was to analyze the color alterations performed by the CIE L*a*b* system in the digital imaging of shade guide tabs, which were obtained photographically according to the automatic and manual modes. This study also sought to examine the observers' agreement in quantifying the coordinates. Four Vita Lumin Vaccum shade guide tabs were used: A3.5, B1, B3 and C4. An EOS Canon digital camera was used to record the digital images of the shade tabs, and the images were processed using Adobe Photoshop software. A total of 80 observations (five replicates of each shade according to two observers in two modes, specifically, automatic and manual) were obtained, leading to color values of L*, a* and b*. The color difference (AE) between the modes was calculated and classified as either clinically acceptable or unacceptable. The results indicated that there was agreement between the two observers in obtaining the L*, a* and b* values related to all guides. However, the B1, B3, and C4 shade tabs had AE values classified as clinically acceptable (Delta E = 0.44, Delta E = 2.04 and Delta E = 2.69, respectively). The A3.5 shade tab had a AE value classified as clinically unacceptable (Delta E = 4.17), as it presented higher values for luminosity in the automatic mode (L* = 54.0) than in the manual mode (L* = 50.6). It was concluded that the B1, B3 and C4 shade tabs can be used at any of the modes in digital camera (manual or automatic), which was a different finding from that observed for the A3.5 shade tab.
Keywords: Tooth; Color Perception; Image Processing, Computer-Assisted